2002
DOI: 10.4049/jimmunol.169.10.5986
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of TRAIL and TRAIL Receptors in Allergic Asthmatics Following Segmental Antigen Challenge: Evidence for a Role of TRAIL in Eosinophil Survival

Abstract: Asthma is a chronic lung disease exhibiting airway obstruction, hyperresponsiveness, and inflammation, characterized by the infiltration of eosinophils into the airways and the underlying tissue. Prolonged eosinophilic inflammation depends on the balance between the cell’s inherent tendency to undergo apoptosis and the local eosinophil-viability enhancing activity. TRAIL, a member of the TNF family, induces apoptosis in most transformed cells; however, its role in health and disease remains unknown. To test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 40 publications
2
67
2
Order By: Relevance
“…In a mouse model of asthma, increased expression of TRAIL was shown to be responsible for increased apoptosis of airway leukocytes and associated with the resolution of allergy through a reduction in Th2 production of IL-5 (51). In human asthma, a higher BAL eosinophil count is associated with a decreased expression of the canonical TRAIL death receptors (52). Conversely, TRAIL signaling has also been linked to nonapoptotic and proliferative events (52)(53)(54), thus indicating that further investigation into the role of TRAIL after BT is necessary to establish its function.…”
Section: C/fpomentioning
confidence: 99%
“…In a mouse model of asthma, increased expression of TRAIL was shown to be responsible for increased apoptosis of airway leukocytes and associated with the resolution of allergy through a reduction in Th2 production of IL-5 (51). In human asthma, a higher BAL eosinophil count is associated with a decreased expression of the canonical TRAIL death receptors (52). Conversely, TRAIL signaling has also been linked to nonapoptotic and proliferative events (52)(53)(54), thus indicating that further investigation into the role of TRAIL after BT is necessary to establish its function.…”
Section: C/fpomentioning
confidence: 99%
“…102 In addition, several other mechanisms have been reported to contribute to these effects of TRAIL, such as activation of NF-kB, insulin-like growth factor type 1 receptor (IGF1R) and SP-1. 103,104 Furthermore, TRAIL could stimulate p38-dependent INFg secretion and proliferation in T cells, 105 enhance survival signaling in eosinophils of asthma patients, 106 and stimulate ERK1/2 and Akt-dependent survival of fibroblast-like synoviocytes derived from rheumatoid arthritis patients. 107 Interestingly, also a role for TRAIL signaling has been found in the differentiation of different cell types.…”
Section: Non-apoptotic Trail Signaling In Non-transformed Cellsmentioning
confidence: 99%
“…Inflammation in BD is thought to be mediated by cytokines derived from T-helper type 1 lymphocytes, including TNF-α. Increased numbers of monocytes and T cells expressing gammadelta receptors produce extensive amounts of TNF-α, resulting in high levels of circulating TNF-α and soluble TNF receptors in the peripheral blood of the BD patients (15,16).The members of the TNF family play critical roles as prominent mediators of immune regulation and the inflammatory response (18). It was reported that TNF-α related polymorphisms could play an important role in the development of BD.…”
Section: Introductionmentioning
confidence: 99%